Leveraging Healthcare to Promote Responsive Parenting: Impacts of the Video Interaction Project on Parenting Stress - Cates, Carolyn Brockmeyer (J Child Fam Stud, 2015)
We sought to determine impacts of a pediatric primary care intervention, the Video Interaction Project, on 3-year trajectories of parenting stress related to parent-child interactions in low socioeconomic status (SES) families. A randomized controlled trial (RCT) was conducted, with random assignment to one of two interventions (Video Interaction Project [VIP]; Building Blocks [BB]) or control (C). As part of VIP, dyads attended one-on-one sessions with an interventionist who facilitated interactions in play and shared reading through review of videotaped parent-child interactions made on primary care visit days; learning materials and parenting pamphlets were also provided to facilitate parent-child interactions at home. Parenting stress related to parent-child interactions was assessed for VIP and Control groups at 6, 14, 24, and 36 months using the Parent-Child Dysfunctional Interaction subscale of the Parenting Stress Index- Short Form, with 378 dyads (84%) assessed at least once. Group differences emerged at 6 months with VIP associated with lower parenting stress at 3 of 4 ages considered cross-sectionally and an 17.7% reduction in parenting stress overall during the study period based on multi-level modeling. No age by group interaction was observed, indicating persistence of early VIP impacts. Results indicated that VIP, a preventive intervention targeting parent-child interactions, is associated with decreased parenting stress. Results therefore support the expansion of pediatric interventions such as VIP as part of a broad public health strategy to address poverty-related disparities in school-readiness.